Temperament Characteristics of Children in Residential Care and Perceived Acceptance/Rejection and Style of Discipline Used by Care Workers - Gaitán, Sabina D.; Fenández-Sánchez, Joanna; Fernández-Baena, Francisco Javier; Wallace-Ruíz, Agustín; Salas-Martínez, María Dolores (MDPI, 2024)
The ability to adapt interpersonal interactions to temperamental characteristics is essential for high-quality care. We analyzed how temperamental and self-regulation differences among children in residential care were related to the affective relationships and discipline styles of their caregivers. A total of 144 children aged 9–16 years (42.6% boys) and their caregivers from 22 residential care homes (Spain) participated. The Early Adolescent Temperament Questionnaire-Revised (EATQ-R) was used to assess temperament, the Affect Scale and Rules and Demands Scale was used to assess children’s perceptions of affective relationships and discipline styles among their caregivers, and BRIEF-2 was used to assess children’s self-regulation. Perceived warmth/communication was significantly higher than criticism/rejection and children perceived more inductive than rigid or permissive styles. Temperamental-scale fear was positively related to warmth/communication and an inductive style, and negatively related to criticism/rejection and a rigid style, whereas high-intensity pleasure showed the opposite pattern. In addition, some self-regulation and temperament scales explained 26% of the perception of warmth/communication, while others explained 15% of the variability of the rigid discipline style used by care workers. These results can help care workers to adjust their educational strategies according to the temperamental characteristics of this specific population.
Keywords: Acogimiento familar - Aspecto pscológico; Temperament; Residential care; Rejection; Acceptance; Style of discipline